2015
DOI: 10.5127/jep.045314
|View full text |Cite
|
Sign up to set email alerts
|

Automatization and familiarity in repeated checking: A replication

Abstract: Repetitive, compulsive-like checking of an object leads to reductions in memory confidence, vividness, and detail. Experimental research suggests that this is caused by increased familiarity with perceptual characteristics of the stimulus and automatization of the checking procedure (Dek, van den Hout, Giele, & Engelhard, 2014). This suggests that defamiliarization by modifying perceptual characteristics of the stimulus will result in de-automatization and attenuation of the meta-memory effects. However, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Data on the RT task indicated that repeated relevant checking led to significant pre-to-post-test reductions in RT, whereas irrelevant checking did not (cf. Dek et al, 2015). In sum, repeated relevant checking led to automatization of checking behavior, but the specificity of this effect was only evident on the dual RT task, and OCD patients did not differ from non-clinical controls in the automatization pattern.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Data on the RT task indicated that repeated relevant checking led to significant pre-to-post-test reductions in RT, whereas irrelevant checking did not (cf. Dek et al, 2015). In sum, repeated relevant checking led to automatization of checking behavior, but the specificity of this effect was only evident on the dual RT task, and OCD patients did not differ from non-clinical controls in the automatization pattern.…”
Section: Discussionmentioning
confidence: 87%
“…Although our 'moderate' defamiliarization procedure did lead to partial de-automatization (cf. Experiment I by Dek et al, 2015), the perceptual modification might not have been distinct enough to attenuate the detrimental meta-memory effects of re-checking. Dek et al (2015) demonstrated that 'strong defamiliarization' does attenuate the negative meta-memory effects of repeated checking.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations